Changes in pancreatic levodopa uptake in patients with obesity and new-onset type 2 diabetes: an 18F-FDOPA PET-CT study - Kwon, Yeongkeun; Yoon, Hanseok; Ha, Jane; Lee, Hyeon-seong; Pahk, Kisoo; Kwon, Hyunwoo; Kim, Sungeun; Park, Sungsoo (Frontiers in Endocrinology, 2025)
IntroductionLevodopa (L-3,4-dihydroxyphenylalanine)g, a dopamine precursor that circulates in the peripheral region, is involved in pancreatic glycemic control. Although previous animal studies have shown that peripheral levodopa is correlated with insulin secretion in pancreatic beta cells, the mechanism by which the pancreas uses levodopa differently in humans with obesity and type 2 diabetes remains unknown. Our study aimed to observe how the pancreas uptakes and utilizes levodopa differently under obese and diabetic conditions.Materials and method18F-fluoro-L-dopa positron emission tomography-computed tomography (18F-FDOPA PET-CT) was used to visualize how the human body uses levodopa under obese and diabetic conditions and presented its clinical implications. 10 patients were divided into 3 groups: 1) Group A, normal weight without type 2 diabetes; 2) Group B, obese without type 2 diabetes; and 3) Group C, obese with new-onset type 2 diabetes. All patients’ lifestyle modification was conducted prior to 18F-FDOPA PET-CT, and plasma samples were collected to confirm changes in amino acid metabolites.ResultsPancreatic levodopa uptake increased in obese patients with insulin resistance, whereas it decreased in obese patients with new-onset type 2 diabetes [standardized uptake value (SUV) mean in participants with normal weight, 2.6 ± 0.7; SUVmean in patients with obesity, 3.6 ± 0.1; SUVmean in patients with obesity and new-onset type 2 diabetes, 2.6 ± 0.1, P = 0.02].ConclusionsThis suggested that the alterations in the functional capacity of pancreatic beta cells to take up circulating levodopa are potentially linked to the insulin resistance and the pathogenesis of type 2 diabetes. The differences in the uptake values between the groups implied that pancreatic levodopa uptake could be an early indicator of type 2 diabetes.